Pengaruh Keinformatifan Laba, Perataan Laba, dan Struktur Modal Tehadap Nilai Perusahaan dengan Dimoderasi Kemampuan Manajerial - Fayza Maharani Az Zahra; Barlia Annis Syahzuni (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to empirically examine the effect of earnings informativeness, income smoothing, and capital structure on firm value, with managerial ability as a moderating variable. The research is grounded in signaling theory, which emphasizes that the quality of financial information and financial decisions serve as important signals in shaping investor trust and perceptions. The research design applies a causal approach with a quantitative method. The study focuses on industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. From a total of 67 firms, 45 were selected as the sample using purposive sampling based on consistent listing criteria and financial reporting in Indonesian rupiah, resulting in 135 panel data observations. The analysis employed Chow, Hausman, and Lagrange Multiplier tests to determine the most appropriate model, with estimation conducted using the Random Effects Model (REM) adjusted by robust standard errors. The moderating effect was tested using Moderated Regression Analysis (MRA). The findings reveal that earnings informativeness has no significant impact on firm value, while income smoothing and capital structure show a significant positive effect. Managerial ability was found to weaken the relationship between income smoothing and firm value but did not moderate the relationship of earnings informativeness or capital structure with firm value. Overall, these results highlight the importance of effective capital structure management and transparent earnings reporting as positive signals for investors, while managerial ability plays a more selective role in influencing market responses to corporate information.